Isolation, Identification and Antioxidant Potential of Major Flavonoids from Ethyl Acetate Fraction of Torreya grandis - Khalid Saeed, M.; Naeem Khan, M.; Ahmad, Ijaz; Hussain, Naqi; Ali, Sakhawat; Deng, Yulin; Dai, Rongji (Asian Journal of Chemistry, 2012)
There is increasing interest in plant extracts as potential therapeutic agents and the use of a mixture of natural products to treat disease has a number of interesting outcomes, most notably their synergistic effects and polypharmacological action. Some flavonoids with antioxidant properties from the aerial parts of the plant species Torreya grandis (family Taxaceae) were identified. Upon chromatography, the ethyl acetate extract afforded flavonoids, such as: 4',5,7-trihydroxy flavone-5-O-[a-L-rhamnopyranosyl-(1-4)-6-O-acetyl-b-D-glucopyranoside] (1), apigenin-7-O-b-glucopyranoside (2), apigenin (3), luteolin (4) and chrysin (5). The structures of the isolated compounds were determined by interpretation of their physical and spectral data. The antioxidant activities of water and 80 % ethanol extracts were measured by FRAP, 2,2'-diphenylpicrylhydrazyl (DPPH•) and reducing power activity methods, while the antioxidant activities of isolated compounds were estimated by TEAC assay. The 80 % ethanol extract and isolated compound luteolin showed a strong concentration-dependent antioxidant effect than commercial antioxidant a-tocopherol. This investigation demonstrated that the plant species T. grandis is a new and favourable source of natural antioxidants and the potency of these compounds could provide a chemical basis for some of the health benefits claimed for T. grandis in folk medicine and warrant further studies to assess their potential as effective natural remedies.